Project on Human Development in Chicago Neighborhoods (PHDCN): Family Legal Update, Wave 2, 1997-2000 - Earls, Felton J. ([Verlag nicht ermittelbar], 2005)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Family Legal Update administered to the primary caregivers of subjects belonging to Cohorts 0 to 15 and to the subjects, themselves, in Cohort 18. It included questions designed to obtain any family member's involvement with the law since the Wave 1 interview (PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): FAMILY MENTAL HEALTH AND LEGAL HISTORY, WAVE 1, 1994-1997 [ICPSR 13591]).